Long-range magnetic order in the porous metal–organic framework Ni(pyrazine)[Pt(CN)4]. Issue 43 (23rd October 2017) - Rodríguez-Velamazán, J. Alberto; Roubeau, Olivier; Poloni, Roberta; Lhotel, Elsa; Palacios, Elías; González, Miguel A.; Real, José A.
Abstract : Long-range magnetic ordering is demonstrated in {Ni(pyrazine)[Pt(CN)4 ]}, which opens new perspectives for multifunctionality in this class of porous coordination compounds. Abstract : A combined study involving DFT calculations, neutron scattering, heat capacity and magnetic measurements at very low temperatures demonstrates the long-range magnetic ordering of Ni(pyrazine)[Pt(CN)4 ] below 1.9 K, describing its antiferromagnetic spin arrangement. This compound belongs to the family of porous coordination polymers M(pyrazine)[Pt(CN)4 ] (M = divalent metal), renowned for showing interesting combinations of porosity and magnetic properties. The possibility of including long-range magnetic ordering, one of the most pursued functional properties, opens new perspectives for the multifunctionality of this class of compounds.